Negotiating land for flood risk management : upstream‐downstream in the light of economic game theory. Issue 1 (12th September 2017) - Machac, J.; Hartmann, T.; Jilkova, J.
Abstract : This paper discusses the use of game theory as a method to achieve land and water governance for flood retention and resilience on a catchment scale. Therefore, it addresses flood retention in river catchments by using pay‐off matrices of game theory. How do pay‐off matrices between upstream and downstream change when certain property rights are adjusted or institutional conditions are changed? What if liability issues, responsibilities, and externalities of flood protection measures are reframed? Who should pay and who profit from retention measures? Individual scenarios correspond to some basic games from the game theory. The aim of these thought experiments is to develop rules for upstream‐downstream agreements on retention and resilience within a river basin area.